Ergebnisse der Albanien-Expedition 1961 des ’Deutschen Entomologischen Institutes’. 84. Beitrag. Coleoptera: Erotylidae. - Delkeskamp, Kurt; Friese, Gerrit (Contributions to Entomology = Beiträge zur Entomologie, 1971)
The Erotylidae collected by the expedition to Albania by Deutsches Entomologisches Institut were evaluated the material, which was supplemented by 2 individuals collected by A. Bischoff, included 7 individuals of 4 species. All 4 species were first finds in Albania; no previous or additional finds of Erotylidae on this territory have come to the author’s knowledge. A survey of their distribution is given which lists 22 species of this family on the Balkan peninsula.